Productivity and Economics of Sorghum Varieties for Grain as Influenced by Nitrogen Levels in Sandy Loam Soil - Namoobe, Cleto; Nanwal, R.K; Kumar, Pawan (International Journal of Natural Sciences Research, 2014)
The experiment was carried out at the Student Farm of CCS HAU, Hisar for two consecutive kharif seasons of 2011 and 2012. The field was laid out in a split plot design following the block randomization system with three replications. Four varieties (HC 541, HC 308, HC 171 and HJ 513) and five nitrogen levels (0, 40, 60, 80 and 100 kg N ha-1) were taken in the main plots and subplots, respectively. Data collected revealed that varieties and nitrogen levels has a significant influence on panicle length, number of grains panicle-1, test weight and grain yield in both the years. Variety HJ 513 gave the maximum panicle length (28.4 and 29.6 cm), highest number of grains panicle-1 (1385 and 1402), test weight (17.60 and 24.33g) and grain yield (1949 and 1938 kg ha-1) in both the years. The overall economic optimum nitrogen rate (EONR) was found to be 139.1 kg ha-1 for all the varieties. However, each individual variety showed the following EONR: HJ 541 (143.1 kg ha-1), HC 308 (144.4 kg ha-1), HC 171 (139.3 kg ha-1) and HJ 513 (131.5 kg ha-1). The application of 100 kg N ha-1 gave the highest net returns and BC ratio. Variety HJ 513 had the highest BC ratio (2.24 and 2.01) in both years.